2010
DOI: 10.1128/aem.01427-09
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of the Lactobacillus acidophilus Surface Layer and Nisin on Bacterial Growth

Abstract: We have previously described a murein hydrolase activity for the surface layer (S-layer) of Lactobacillus acidophilus ATCC 4356. Here we show that, in combination with nisin, this S-layer acts synergistically to inhibit the growth of pathogenic Gram-negative Salmonella enterica and potential pathogenic Gram-positive bacteria, Staphylococcus aureus and Bacillus cereus. In addition, bacteriolytic effects were observed for the Gram-positive species tested. We postulate that the S-layer enhances the access of nisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
(18 reference statements)
2
29
0
Order By: Relevance
“…Thus, in combination with nisin, S-layer acts synergistically to inhibit the growth of S. Newport (Prado-Acosta, Ruzal, Allievi, Palomino, & Sanchez Rivas, 2010). A similar effect was observed when cooked ham and bologna were coated with gelatin gel containing 25.5 g/l of lysozyme-nisin (1:3) plus 25.5 g/l of EDTA (Gill & Holley, 2000).…”
Section: Association Of Bacteriocins With Other Chemical Treatmentssupporting
confidence: 59%
“…Thus, in combination with nisin, S-layer acts synergistically to inhibit the growth of S. Newport (Prado-Acosta, Ruzal, Allievi, Palomino, & Sanchez Rivas, 2010). A similar effect was observed when cooked ham and bologna were coated with gelatin gel containing 25.5 g/l of lysozyme-nisin (1:3) plus 25.5 g/l of EDTA (Gill & Holley, 2000).…”
Section: Association Of Bacteriocins With Other Chemical Treatmentssupporting
confidence: 59%
“…The SLPs of L. acidophilus ATCC 4356 were reported to have the ability to inhibit the growth of S. enterica serovar Newport, but not that of Staphylococcus aureus or Bacillus cereus when applied alone; however, they acted synergistically with nisin to inhibit the growth of the two latter. It was therefore postulated that SLPs enhance the access of nisin into the cell membrane by enabling its transport through the cell wall, while nisin provides ion-nonspecific dissipation of the proton motive force that contributes to the murein hydrolase activity of SLPs [13].…”
Section: Resultsmentioning
confidence: 99%
“…The SLPs of L. acidophilus ATCC 4356 that were extracted by lithium chloride were able to hydrolyse the cell wall peptidoglycan of Escherichia coli, Micrococcus luteus and Salmonella enterica serovar Newport [12], thereby inhibiting the growth of pathogens and acting synergistically with nisin to reduce the levels of gramnegative and gram-positive bacteria [13]. Previous studies had reported that a pulsed electric field (PEF) could change the peptidoglycan layer of E. coli and expose the plasma membrane, but the intracellular enzyme and cellular metabolic activities remained active, indicating sublethal injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…At high quantities, this process can be divided into two stages, with the first being bacteriostatic and the second bactericidal [3,33,38]. Nisin has also been found to act as a lytic agent [39].…”
Section: Page 8 Of 40mentioning
confidence: 99%